ACTIVITY OF CHLORHEXIDINE ASSOCIATED WITH SILVER NANOPARTICLES AGAINST Candida albicans BIOFILMS ON TOOTHBRUSHES: Atividade da clorexidina associada com nanopartículas de prata contra biofilmes de Candida albicans em escovas dentais - de Almeida Mendes, Cecilia Maria; Fernandes Barcelos, Aline; Simões Chagas da Silva, João Salviano; Rebelo Guilherme, Luciana; Naves, Plínio (Revista Interfaces: Saúde, Humanas e Tecnologia, 2025)
The yeast Candida albicans is a normal constituent of the human microbiota with considerable pathogenicity and ability to form microbial biofilms in various anatomical sites, including the oral cavity. Chlorhexidine is an antiseptic widely used against Gram-positive and Gram-negative bacteria, fungi, yeasts, and lipophilic viruses. Silver nanoparticles (AgNPs) have shown potential antiseptic effects against yeasts. In this context, this study aimed to evaluate the activity of chlorhexidine gluconate and silver nanoparticles against Candida albicans ATCC 10231 inoculated on sterilized toothbrushes. Previously inoculated toothbrushes were exposed to the compounds at room temperature for 20 minutes for the initial 1-hour adhesion test, and for 1 hour against mature biofilms cultured for 48 hours at 35.5 °C, then the samples were diluted and plaqueted for the quantification of viable yeasts after treatment. The most significant reduction in yeast viability was observed with the combination of chlorhexidine and AgNPs, with 97.2 % in the initial adherence test and 77.2 % against biofilms. This finding suggests a synergistic effect between the compounds against Candida albicans, with a more pronounced effect against the planktonic state than against mature biofilms.